A rare case of posterior circulation stroke with anterior spinal artery involvement - Pandian T. K., Rajasekara; S., Hemkumar; K., Mugundhan; V., Kannan; R., Viveka Saravannan; Jeyaraj K., Malcolm; S., Sakthi Velayutham; P. R., Sowmini; S., Lakshmanan (International Journal of Research in Medical Sciences, 2025)
A 36 year old gentlemen with diabetes mellitus and systemic hypertension with acute onset giddiness with weakness of both upper limbs, developed over a period of several hours with bilateral triceps weakness, wrist dorsiflexion and palmar flexion weakness with no sensory disturbance and cerebellar signs. MRI brain showed left cerebellar infarct, left lateral medullary infarct, non- visualization of left vertebral artery, T2 hyper-intensity of cervical cord from 4th cervical segment to 8th cervical segment, multiple areas are affected because of left vertebral artery occlusion.